The Impact of Applying Green Marketing Dimensions on Preserving The Environment According to Vision 2030, The Case of Northern Region Cement Company (NRC) - AL-Ghaswyneh, Dr. Odai Falah Mohammad (The journal of contemporary issues in business and government, 2021)
The study exploresthe impact of applying green marketing dimensions on preserving the environment, according to vision 2030, the case of the Northern Region Cement Company (NRC). The research follows the descriptive, analytical approach to describe the research topic, present the research literature and its theoretical framework, define the research problem, analyze the questionnaire, and the results of the research The environmental axis of the vision was to make business organizations in the Kingdom work on preserving the environment and the natural capabilities. It is among our responsibilities toward future generations, and a fundamental ingredient in the quality of our lives to work on raising the level of work in the environment, improving the level of services provided that contribute to the safety and welfare of society, and promoting sustainable development, by reducing pollution and by raising the efficiency of violation management, to preserve the environment and our natural capabilities.